Pemanfaatan Sampah Plastik sebagai Bahan Daur Ulang melalui Metode Ecobrick - Raihan, Muhammad; Pradana, Muhammad Yudha; Hakim, Arief Rahman; Fadhil Hasan R, Hans Mokhammad; Chaerani, Ika Tania; Safitri, Saktya Dea; Nurrohmah, Siti; Putri, Hasna Tantowi; Afitri, Windy Dwi; Ananda , Dhimas Aryo Vipha (Prosiding Seminar Nasional Program Pengabdian Masyarakat, 2025)
The problem of plastic waste in Druju Hamlet, Ngawen District, Klaten Regency, is caused by low public awareness and lack of waste management facilities. This program aims to increase public awareness and skills in plastic waste management through the ecobrick method, which is the compaction of plastic into bottles as an environmentally friendly construction material. Activities include socialization, waste collection and cleaning, making ecobricks, and implementation in the form of an installation of the inscription "HATINYA PKK". The results show that 400 ecobrick bottles have been successfully produced, with increasing community participation every week. The door-to-door method in collecting waste and the involvement of PKK women are the main factors in the success of this program. The obstacles faced are the limited amount of plastic waste collected and the need for technical assistance in making standard ecobricks. This program has the potential to be further developed through advanced training, ecobrick-based product development, and community-based waste management policy advocacy